Multisubstance-Using Probationers and the Odds of Arrest While in the Community - Medina, Justin C. (International journal of offender therapy and comparative criminology, 2020)
Failed drug tests commonly lead to technical violations and revocation hearings for probationers. The current study extends these observations by examining whether multisubstance-using probationers also have increased odds of arrest in the community. This is important as multisubstance-using probationers may present unique public safety challenges to community corrections agencies and require intensive treatment resources and additional monitoring. Using data from a county-level probation cohort (N = 2,257) from 2009 to 2010, a series of logistic regression analyses estimated the effects of multisubstance use on the odds of being arrested for a new offense while in the community. The findings revealed that multisubstance use and the frequency of multisubstance use increased the odds of arrest while on probation when compared with single-substance users. We discuss how agencies may best supervise multisubstance-using probationers and suggest directions for further examination.